TRANSFORMATION OF THE MODEL OF CONSUMER BEHAVIOR IN THE MODERN ECONOMY - Mavlonova Dildora (Scholars Digest Publishing, 2023)
This article aims to explore the shifts in consumer behavior models brought about by technological advancements, globalization, and cultural factors in the modern economy. In focusing on these changes, the paper examines the impact on businesses and policy-making. Specifically, recommendations are offered for adapting to these changes in the context of Uzbekistan's emerging market economy.
Keywords: consumer behavior, modern economy, technology, globalization.